If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-2) = -3y Multiply 6 * -2 -12 = -3y Solving -12 = -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -12 + 3y = -3y + 3y Combine like terms: -3y + 3y = 0 -12 + 3y = 0 Add '12' to each side of the equation. -12 + 12 + 3y = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 3y = 0 + 12 3y = 0 + 12 Combine like terms: 0 + 12 = 12 3y = 12 Divide each side by '3'. y = 4 Simplifying y = 4
| 3(7+2b)=75 | | 6(-2w-10)=60 | | 4(6+5t)=204 | | 2(4w+5)=34 | | 7(-5b+2)=49 | | 2(-7+6k)=-98 | | 6(0)=-3y | | 6(2)=-3y | | 7(3-6k)=-105 | | 3(4k+10)=54 | | 2(5-7d)=24 | | 7(-6-3w)=-210 | | 7(6-4b)=-154 | | 11+2x=55+3x | | .3x-9=.16x-4 | | 6(4t+9)=78 | | 6(7d+5)=240 | | 2(-6n+9)=-6 | | 4(-7-6a)=-148 | | 5(3+7d)=400 | | 6(3a-2)=-120 | | x+1.732050808+3x=18-2x | | -2(-2)+8=y | | 7(-9-7n)=-651 | | -2(0)+8=y | | 6(-9-3a)=162 | | 5(7-2n)=155 | | 3(-7+6b)=-21 | | -2(2)+8=y | | 4(7x+5)=216 | | 7(5n+9)=-7 | | 7(4n-6)=238 |